Studies on Schismatoglottideae (Araceae) of Peninsular Malaysia I: On the identity of Schismatoglottis wallichii var. oblongata and a new name: Schismatoglottis lowae - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2017)
Schismatoglottis lowae S. Y. Wong & P. C. Boyce sp. nov. is described and illustrated based on the type of Schismatoglottis wallichii var. oblongata Hook.f., until now treated as a heterotypic synonym of S. wallichii Hook.f. A key to the three accepted species of hapaxanthic-stemmed (Calyptrata Clade) Schismatoglottis in Peninsular Malaysia is provided.